Peran Audit Internal Dalam Mencegah Fraud Untuk Mewujudkan Good Corporate Governance (Studi Kasus Pada Pt Bukit Asam Tbk) - Andeskara, Saqian Putra; Fachriyah , Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research, conducted on the Corporate Management System and GCG work unit and the Internal Control Unit (SPI) of PT Bukit Asam Tbk, aims to analyze the role of internal audit as the company's internal control system in preventing fraud in the company to achieve Good Corporate Governance (GCG) and to analyze the internal auditor's obstacles in preventing fraud. This study employs a case study qualitative method involving primary data. To test the validity of the data, this study utilizes the data triangulation technique. The results of this study indicated that the internal audit of PT Bukit Asam Tbk had a very important role in anticipating fraud. SPI or internal auditors also implemented the E-Gratification system and WBS (Whistleblowing System) as a preventive action against management and employees committing fraud threatening the company in achieving Good Corporate Governance. For the internal audit process, there are no obstacles in preventing fraud as the company adopts a GCG culture and management commitment to achieving a good company.